Cemento-ossifying fibroma - Rida Zainab; Imtiaz Ali; Hina Naseer; Muhammad Ayub Mansoor; Aiza Sohail Khan; Asad Abbas Jafri (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2022)
Cemento-ossifying fibroma is a rare benign fibro-osseous neoplasm commonly involving the jaws majority of lesions occur in mandible bone. It can be discovered as an incidental finding in radiological imaging. Symptomatic patients are presented with a slowly growing mass involving the jaws commonly in mandible bone and can attain a large size with the passage of time. It can cause facial deformity if left untreated. We present such a case of Cemento-ossifying fibroma involving the right hemi-mandible bone, and its radiological imaging findings, including X-ray (OPG), CT scan, and Histopathology.